A process analysis methodology for enterprise resource planning (ERP) implementation - (:unkn) unknown (PROFESSIONAL ENGINEERING PUBLISHING LTD, 2000)
With ERP through computers and a common database, the work in many different functions of the enterprise can be better coordinated, and volumes of common information can be shared. ERP has sought sophistication but achieved complexity instead. Therefore implementation of ERP applications has become a more complex and expensive issue. In this study, a process analysis methodology for ERP implementation is presented. This methodology consists of the steps necessary to select and define processes on which an ERP implementation will be carried out and the steps to identify the gaps between these processes and the standard processes of the ERP application. The major aim of this methodology is to determine the degree of functional suitability of an ERP application to the business requirements of an enterprise by determining the gaps systematically.